Enhancing Green Growth: Exploring the Influence of Fiscal Spending and Green Finance - Dinh , Le Quoc; Oanh, Tran Thi Kim; Ha, Nguyen Thi Hong (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2025)
The present study delves into the intricate correlation between fiscal spending and green growth, specifically focusing on the catalyzing effect of green finance. Spanning the timeframe from 2005 to 2021, our investigation encompasses 18 developing and 14 developed countries. Leveraging Bayesian regression analysis, our findings uncover a nuanced juxtaposition in the effect of R&D expenditure on green growth across these divergent contexts. In developing nations, R&D spending demonstrates a discouraging negative effect on green growth, supported by a robust probability of 76.74%. Conversely, in developed countries, R&D expenditure manifests a promising positive influence, with a likelihood of 71.33%. However, upon integrating the pivotal role of green finance, a synergistic relationship emerges, underscoring its potential as a catalyst for bolstering green growth in both categories of nations. Grounded in these discerning insights, we delineate tailored implications aimed at fortifying green finance initiatives within each cohort of countries.